PENGARUH EKSPOR IMPOR TERHADAP CADANGAN DEVISA NEGARA STUDI PADA KOMODITI LADA - Hani, Maria Zaun; Pujianto, Agung; Tjahjono, Endro (Jurnal Dinamika Administrasi Bisnis, 2015)
Pepper is one of the main commodities in meeting human needs             so that some countries do import export activities, with the aim of meeting needs in the country and increase the country's income. The purpose of this study is to determine how much influence the activity of export and import of pepper to the development of foreign exchange reserves, to determine the effect of volume andpepper export value to the development of foreign exchange and know the volume and value of imports pepper to the decline in foreign exchange reserves, researchers will indicate simultaneous effect on exports and imports of pepper to the foreign exchange reserves. Research data from using time series from 2000 to 2013. The regression analysis method linear and then using simple linear regression analysis. Statistical Product and Service Solutions (SPSS) were used for analysis.Results of this study shows that Indonesia as a country exporting and importing pepper contributing to the agricultural sector as well as the influence simultaneously of the international reserves position. Keywords: Pepper, export, import and foreign exchange reserves